From genomics to treatment: overcoming pan-drug-resistant Klebsiella pneumoniae in clinical settings - Pasteran, Fernando; Manuel De Mendieta, Juan; Pujato, Natalia; Dotta, Gina; González, Lisandro J.; Rizzo, Mabel; Fernández, Alejandra; Ceriana, Paola; Maccari, Lucia; Rapoport, Melina; Gómez, Sonia; Lucero, Celeste; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe spread pan-drug resistant pathogens pose a critical challenge to current therapies, resulting in high mortality and necessitating alternative approaches.MethodsWe report pan-drug resistant Klebsiella pneumoniae isolates from five patients in a single hospital, including resistance to cefiderocol and cefepime-zidebactam in one isolate.ResultsWhole-genome sequencing identified blaNDM-5 and blaCTX-M-15 genes in all isolates, explaining carbapenemase and extended-spectrum β- lactamase phenotypes, with blaKPC-2 in one isolate. A novel sulfhydryl variable β-lactamase (SHV) variant, blaSHV-231, was present in all isolates under a strong promoter. Two isolates exhibited a non-synonymous mutation in fstI encoding PBP3, the primary target of aztreonam in Gram-negative bacteria. Genomic and phenotypic characterization guided successful compassionate treatment using aztreonam, ceftazidime-avibactam, and amoxicillin-clavulanate at maximum doses.DiscussionDissection of the roles of the substitutions present in blaSHV-231 revealed that this variant was responsible for the reduced susceptibility to aztreonam-avibactam, at the expense of a higher susceptibility to clavulanate. Targeted therapy can be successful upon dissection of unexpected mechanisms of resistance that enhance the contribution of endemic β-lactamase.